226k views
0 votes
Rewrite these powers as a fraction with a positive exponent.

Rewrite these powers as a fraction with a positive exponent.-example-1

1 Answer

3 votes

Given:

The expression in negative exponents is given.

Required:

Write these powers as a fraction with a positive exponent.

Step-by-step explanation:

Use the exponent property


a^(-m)=(1)/(a^m)

(a)


5^(-3)=(1)/(5^3)

(b)


m^(-6)=(1)/(m^6)

(c)


(xy)^(-4)=(1)/((xy)^4)

(d)


\begin{gathered} (-b)^(-2)=(1)/((-b)^2) \\ =(1)/((-1)^2(b)^2) \\ =(1)/(b^2) \end{gathered}

Final Answer:

User Poorya
by
4.4k points